2007
DOI: 10.3818/jrp.9.1.2007.1
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Implementing Automated Risk Assessments in Parole

Abstract: This article describes the efforts undertaken during the past five years for the Georgia Board of Pardons and Paroles to develop a method for assessing parolee risk to inform the supervision level assignments of Georgia's 23,000 active parolees. The project resulted in an actuarial risk assessment method based on the analysis of over 6,000 parolees. Historically, officers conducted pencil-and-paper assessments on all new parolees entering supervision and reassessments every six months thereafter. The new instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 39 publications
1
31
2
2
Order By: Relevance
“…Scally and Newman (2003) observe that unaddressed housing instability among returning offenders does little to break cycles of offending and may present a public safety risk. Indeed, Meredith, Speir, and Johnson (2007) found that each address change made by a parolee increased the likelihood of rearrest by 25 percent. Most recently, Makarios, Steiner, and Travis (2010) and Steiner, Makarios and Travis (forthcoming) also found a positive relationship between frequent residential changes and the probability of rearrest, net of other factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scally and Newman (2003) observe that unaddressed housing instability among returning offenders does little to break cycles of offending and may present a public safety risk. Indeed, Meredith, Speir, and Johnson (2007) found that each address change made by a parolee increased the likelihood of rearrest by 25 percent. Most recently, Makarios, Steiner, and Travis (2010) and Steiner, Makarios and Travis (forthcoming) also found a positive relationship between frequent residential changes and the probability of rearrest, net of other factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More than a tendency to reoffend, this finding might denounce the inadequacy of actuarial measures used to assign parolees to levels of supervision (Holtfreter et al, 2004). While some scholars support the use of these measures (Meredith, Speir, & Johnson, 2007), others express concerns (Hardyman & Van Voorhis, 2004) that they assign women to parole conditions that are stricter than necessary, leading to more violations of parole agreements. Seiter (2014) indicates that female offenders are often "overclassified" since most risk assessment measures are not validated on female offender populations (Hardyman & Van Voorhis, 2004as cited in Seiter, 2014.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Completing rehabilitation programming may reduce offenders' odds of engaging in deviance because treatment may equip them with skills that enhance human capital and facilitate the adoption of prosocial roles (Committee on Community Supervision and Desistance from Crime, 2008;MacKenzie, 2000;Travis & Visher, 2005;Visher & Courtney, 2007). Findings from related studies suggest that offenders who are employed or have more stable residential situations have lower odds of recidivism (DeJong, 1997;Gendreau, Little, & Goggin, 1996;Griffin & Armstrong, 2003;MacKenzie & De Li, 2002;Meredith, Speir, & Johnson, 2007;Uggen et al, 2005;Visher & Courtney, 2007;Wooldredge & Thistlethwaite, 2002). Evidence regarding the effectiveness of rehabilitation programs in general is varied (Committee on Community Supervision and Desistance from Crime, 2008; Drake, Aos, & Miller, 2009;Petersilia, 2003); however, reviews of evaluations of treatment programs have revealed that some programs work for some offenders some of the time (MacKenzie, 2006;Petersilia, 2003).…”
mentioning
confidence: 91%